2014
DOI: 10.4067/s0717-73562014000300007
|View full text |Cite
|
Sign up to set email alerts
|

Entre Lo Aymara Y Lo Chileno: Escala De Involucramiento en La Cultura Aymara (Eica). Una Aproximación Interdisciplinar a La Dimensión Aymara en La Vivencia Intercultural De Estudiantes De Enseñanza Básica Del Norte De Chile

Abstract: Los autores ofrecen un análisis del proceso de génesis y de la posterior implementación de una herramienta metodológica fundamental en la fase constitutiva de un estudio interdisciplinar en relación con el bienestar psicológico de niños de origen aymara en contextos de escolarización en la ciudad de Arica, en el norte de Chile. Esta zona se caracteriza por situaciones interculturales bastante marcadas entre lo que, de manera simplificada, se podría denominar una cultura hegemónica nacional-chilena y una cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…Inventory of the Level of Involvement in Aymara Culture – Escala de Involucramiento en la Cultura Aymara (EICA) [ 61 ]: This instrument measures a child’s level of involvement in Aymara culture. The development of this scale was carried out by the authors of the study who an epidemiologist, a clinical psychologist and an anthropologist.…”
Section: Methodsmentioning
confidence: 99%
“…Inventory of the Level of Involvement in Aymara Culture – Escala de Involucramiento en la Cultura Aymara (EICA) [ 61 ]: This instrument measures a child’s level of involvement in Aymara culture. The development of this scale was carried out by the authors of the study who an epidemiologist, a clinical psychologist and an anthropologist.…”
Section: Methodsmentioning
confidence: 99%
“…[los] niños y adolescentes pertenecientes a esta etnia [aymará], además de presentar un menor rendimiento académico, muestran a menudo una percepción de sí mismos con una apariencia personal negativa, lo que, en términos psicológicos, podría estar relacionado con procesos de alienación y discriminación (Caqueo-Urízar, De Munter, Urzúa, & Saiz, 2014;antropología).…”
Section: Noción De Sujeto/objetounclassified
“…Para el caso de los estudios cuantitativos, se reconoce un fuerte énfasis en la medición a partir del uso de escalas que buscan operacionalizar y medir aspectos psicosociales implicados en el surgimiento de problemas que afectan a la niñez, sobre todo, en contextos educacionales (Alfaro et al, 2016;Álvarez, Briceño, Álvarez, Abufhele, & Delgado, 2018;Caqueo-Urízar, De Munter, Urzúa, & Saiz, 2014;Casas et al, 2015;Gorostegui & Dörr, 2005;Haquin, Larraguibel, & Cabezas, 2004;Quintana & Muñoz, 2010;Santelices et al, 2012;Urzúa, Caqueo-Urízar, Albornoz, & Jara, 2013;).…”
Section: Metodologíasunclassified
“…At the contextual level, it has been observed that factors such as environmental conflicts, the irruption in their ancestral lands, the displacement (Luque et al, 2016; Snodgrass et al, 2017) and the colonialist structure still prevailing (Pelcastre-Villafuerte et al, 2020), negatively affect the well-being of indigenous people. At the individual level, it has been found that cultural involvement—understood as the participation in traditional activities or the use of the native language (Caqueo-Urízar et al, 2014; Carlson & Güler, 2018; Dockery, 2011)—has a positive effect on the well-being of indigenous people (Hapeta et al, 2019; Kirmayer, 2015; Lindstedt et al, 2017), also playing a key role in the process of development of ethnic identity and influencing the assessment and affective bond established with the reference group (Phinney, 1992).…”
Section: Introductionmentioning
confidence: 99%